The Difference of Students’ Learning Outcomes through the Implementation of Cooperative Learning Model Two Stay Two Stray type based Concept Maps with Problem Based Learning at MAN 2 Palu - Kokou, Rizka Kurniawati; Said, Irwan; Mustapa, Kasmudin (Jurnal Akademika Kimia, 2019)
This study was conducted to determine the difference of students’ learning outcomes through the implementation of cooperative learning model two stay two stray type based concept maps with problem based learning at MAN 2 Palu. This study is pre experimental research with static group pre-test post test design. The population was all students of class X MIA at MAN 2 Palu registered in the academic year 2016/2017 as many as 6 classes with a total of 156 students. The sampling technique was purposive sampling. The sample in the experimental class 1 was as much as 27 students, and in the experiment class 2 was as much as 29 students. Data of students’ learning outcomes were tested using mean value, N-gain, and Mann-Whitney U-Test. The results of data analysis showed that the mean value ( ) of students in the experimental class 1 was 83.70, and the mean value ( ) of the experimental class 2 was 76.0. The N-gain value in the experimental class 1 obtained the high criteria gain index of 70.37%, the medium criteria gain index of 25.92%, and the low criteria gain index of 3.70%, while in the experimental class 2 obtained the high criteria gain index of 34.48%, the medium criteria gain index of 58.62%, and the low criteria gain index of 6.89%. The Mann-Whitney U-Test obtained Sig. 2-tailed (0.028) <0.05 and Zaccount (-2.200) < Ztable (-1.96), then H0 is rejected and Ha accepted. It can be concluded that there is a difference in students’ learning outcomes through the implementation of cooperative learning model type two stay two stray based concept maps with problem based learning at MAN 2 Palu.